2022
DOI: 10.1155/2022/6324447
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Apical Periodontitis of the Mandibular First Molar with the Accessory Canal in the Furcation Area Mimicking Furcation Perforation

Abstract: Apical periodontitis frequently presents as a chronic disease. To arrive at a true diagnosis, in addition to the clinical examination, it is mandatory to undertake radiographic examinations and evaluate the clinical presentation. Knowledge of the root canal morphology is a prerequisite for effective nonsurgical endodontic treatment. The internal morphological features of the pulp chamber are variable and complex. This case report describes the treatment and outcome of symptomatic apical periodontitis of a mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…No significant correlation was noted between lesion size and location in the present study; however, the majority of lesions were apical lesions in both jaws, which was expected, since the path of odontogenic infections is through the main canal to the apex [ 25 , 28 ]. In addition, a study of the prevalence of accessory canals in different parts of the teeth revealed that 74% of accessory canals are in the apical third, 15% are in the cervical third, and 11% are in the middle third; thus, higher frequency of apical lesions is justified [ 29 , 30 ]. Meng et al [ 10 ] evaluated the correlation of roots and endodontic lesions in the sagittal plane and reported that root and radicular cysts mostly had a centripetal relationship, and only a small number of cysts had horizontal expansion towards the palatal or buccal surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant correlation was noted between lesion size and location in the present study; however, the majority of lesions were apical lesions in both jaws, which was expected, since the path of odontogenic infections is through the main canal to the apex [ 25 , 28 ]. In addition, a study of the prevalence of accessory canals in different parts of the teeth revealed that 74% of accessory canals are in the apical third, 15% are in the cervical third, and 11% are in the middle third; thus, higher frequency of apical lesions is justified [ 29 , 30 ]. Meng et al [ 10 ] evaluated the correlation of roots and endodontic lesions in the sagittal plane and reported that root and radicular cysts mostly had a centripetal relationship, and only a small number of cysts had horizontal expansion towards the palatal or buccal surface.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the frequency of furcal and furcal to apical lesions was significantly higher in the mandible than maxilla, which was expected considering the root anatomy of mandibular and maxillary molars, since the roots are more divergent in the mandible and dentin thickness is thinner at the furcation site. Moreover, several accessory foramina are present in the furcation area of mandibular molars, which cannot be cleaned and shaped [ 30 ]; thus, the risk of developing furcal lesions is higher in the mandible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the structure of teeth, their sensitive part, which is the pulp and the root canal system, is an intact place to which both pathogens and commensal bacteria in the oral cavity should not have access [ 6 , 7 ]. When the dentinal barriers are damaged by caries, fissures, or trauma, both opportunistic and pathogenic microorganisms gain access to the pulp chamber and root canal system to which they should never have access [ 8 , 9 , 10 ]. This situation could lead to harmful effects such as inflammation, pulp necrosis, and periodontitis [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%